DIGITAL TRANSFORMATION THROUGH TECHNOLOGY ACCEPTANCE MODEL ADOPTION FOR SME RECOVERY ECONOMY DURING THE COVID-19 PANDEMIC - Astiti, Ni Putu Yeni; Prayoga, I Made Surya; Imbayani, I Gusti Ayu (Universitas Brawijaya, Indonesia, 2023)
Because it is anticipated that small and medium-sized businesses will be able to move the economy during the COVID-19 pandemic significantly, they are essential to the economy's recovery. Small and Medium Enterprise must be equipped with the ability and knowledge to adopt technology so that the business is run with added value and can stimulate capital owners to flow their capital to business people so that it can provide a multiplier effect on the economy as a whole, especially in the city of Denpasar. In order to better understand TAM, this study looked at the direct and indirect results of perceived risk, perceived ease of use, and perceived usefulness on both user behavior and intention to use. The sample in this study was 200 SMEs affected by Covid-19 in Bali and used the SEM test with the help of the Stata analysis tool version 16. Intention to use is affected by ease of use and perceived risk. User behavior is affected by intent to utilize. The intention to utilize is not affected by the perceived utility. Perceived usefulness cannot mediate the impact of perceived ease of use on intention to use. Intention to use can mediate the effect of perceived ease of use and perceived usefulness on usage behavior, while the intention to use cannot mediate the impact of perceived risk on usage behavior. The study's findings indicate that the accessibility of technology and the hazards associated with its use are important factors in influencing individuals' intentions to utilize technology. The ability of SMEs to progress in technology is crucial, and technology usability is crucial.